Intertidal caprellids (Crustacea: Amphipoda) of the Persian Gulf and the Gulf of Oman, with description of three new species - Momtazi, Farzaneh; Sari, Alireza (Zootaxa, 2013)
In the present contribution, intertidal caprellids of the Persian Gulf and the Gulf of Oman were studied. Materials were collected, from 40 localities, with a variety of habitats, along the Iranian coasts. Three new species are described including; Metaprotella macoranicus sp. nov, Monoliropus kazemii sp. nov, Pseudaeginella hormozensis sp. nov and Pseudocaprellina pambanensis is reported from studied area. Metaprotella macoranicus sp. nov., is characterized with clear suture between head and pereonite 1, second peduncle article larger than third ones in first antenna, tuft and three long setae in abdominal appendages and reduced mid-dorsal projections in pereonite 3. Monoliropus kazemii sp. nov., possesses biarticulate abdominal appendage, straight second male gnathopod and setal formula with two apical and two medial setae. The main diagnostic character of Pseudaeginella hormozensis sp. nov., is reduced dorsal projection, bearing mid-lateral projection on pereonite 2–5 and robust pereopod 5 with grasping spines on propodus.